Repressed spaces the poetics of agoraphobia - Carter, Paul 1951- (London Reaktion, 2002)
"In repressed spaces Paul Carter tours the cultural history of agoraphobia, the fear open space. There have been many attempts to explain and treat the condition: urban designers have linked it to bad city planning; psychoanalysts, calling it 'street panic', have blamed it on the Oedipus complex; psychiatrists have tied it to existential insecurity; feminists have rooted it in the violence of the male gaze; sociologists have called it a fear of the 'market-place' of late capitalist conspicuous consumption." -- Provided by publisher
Includes bibliographical references (pages 237-246) and index.
Keywords: Agoraphobia -- History; Agoraphobia in literature; Agoraphobia -- Social aspects; Space (Architecture) -- Psychological aspects